A STUDY OF THE SURVEY FOR ANGIOSPERMIC FLORA OF YOUR LOCALITY - CHANDANI KUMARI (International Journal of Multidisciplinary Research and Studies, 2020)
These plants are referred to as mesophytes. Eg: Maize. Xerophytes are plants that do well in dry or arid environments, therefore the name describes them perfectly. Eg: Cactus The vast biological diversity that is manifested at all levels of the biosphere, including the genetic, species, and ecosystem levels, is what we refer to when we talk about biodiversity. It offers the vital products and services that are necessary for the continued existence of human beings as well as other creatures that live on our planet. However, the over use of natural resources has led to a precipitous decline in the availability of these bounties provided by Mother Nature. Burning plastics and other materials that release greenhouse gases, burning fossil fuels, releasing CFCs from various sources such as automobile exhausts, air conditioning vents, refrigerators, and other appliances, along with massive deforestation and the destruction of natural topography, have accelerated the rate at which climate change is occurring on a global scale to an alarming degree. These included the plant's habit and habitat, the colour of its flowers and fruits, the date of collection, any local names given to the plant (if any), phenological data, associated plants, the status of any endangered plants, and the type of forest. leaves usually with reticulate venation; blooms tetra-pentamerous, if trimerous then plants woody.